Time-dependent spin injection. (December 2021) - Bebenin, N.G.
Abstract: Spin injection from ferromagnet into nonmagnetic semiconductor is theoretically investigated for the case when the electric current in ferromagnet/semiconductor structure depends on time. The study of switching on/off dc current showed that the time dependence of the magnetization at any point inside semiconductor does not obey the exponential law with spin relaxation time τs .